Comprehensive analysis of mRNA and miRNA differential expression profiles in the hypothalamus-pituitary-gonadal axis in laying and broodiness period of Wanxi white geese - Xinwei Tong; Xiaojin Li; Yuhua Wang; Fei Xie; Ruidong Li; Man Ren; Qianqian Hu; Shenghe Li (Poultry Science)
The hypothalamus-pituitary-gonadal (HPG) axis is an important neuroendocrine regulatory center involved in egg-laying process in poultry. However, its mechanism of regulating broodiness behavior and laying performance in geese remains unclear. This study explored the molecular mechanism by which the HPG axis regulates brooding behavior in Wanxi white geese (WWG). The hypothalamus, pituitary, and ovarian tissues of Wanxi white geese were collected at laying and brooding periods for transcriptome sequencing analysis. A total of 240 (BH vs. LH), 319 (BP vs. LP), and 445 (BO vs. LO) differentially expressed genes, and 56 (BH vs. LH), 82 (BP vs. LP), and 48 (BO vs. LO) differentially expressed miRNAs were identified. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analysis showed that differentially expressed genes (DEGs) and differentially expressed miRNAs (DEMs) were significantly enriched in hormone level regulation, cell communication, calcium signaling pathway, GnRH signaling pathway, MAPK signaling pathway, Wnt signaling pathway, and other processes. Six DEGs and four DEMs were randomly selected for real-time fluorescence quantitative reverse transcription PCR (RT-qPCR). The results showed that the transcriptome sequencing data were accurate and reliable. In addition, 22 potential hub miRNAs were screened. Dual luciferase reporter assays confirmed the targeting relationship between miR-144-y and DIO3. The results showed that the miRNAs mainly regulated the laying performance and brooding behavior of WWG by mediating the expression of target genes. In this study, we systematically elucidated the mechanisms by which the HPG axis regulates the broodiness behavior and laying performance of WWG at the post-transcriptional level. Several miRNAs and mRNAs associated with the reproductive performance of WWG were identified, providing a crucial reference for the subsequent use of gene editing technologies to breed new varieties and advance the development of WWG breeding industry.